Dynamics of the History of Indonesian Legal System in Legal Transformation in Various Periods - Purnamasari, Putri (Innovative: Journal Of Social Science Research, 2024)
The impact of Dutch colonial law on post-independence Indonesian legal system growth and the role of global and local values in shaping national legal policy are both examined in this historical context. The difficulties in developing a separate national legal system and the inherent duality of Dutch law and customary law are the primary obstacles. Examining the development of the legal system from the colonial to the reform era, this research employs a normative legal technique with a literature-based approach. The study's findings reveal that, despite Indonesia's independence, the country's legal system is heavily influenced by colonial law, particularly in the areas of civil and criminal law. On the other hand, changes to the law that started in the late 90s sought to include both local and international norms and values while eradicating colonial effects. There is ongoing discussion in Indonesian law reform over the difficulties of balancing these two factors.